Vitamin D Responsive Elements within the HLA-DRB1 Promoter Region in Sardinian Multiple Sclerosis Associated Alleles - Cocco, Eleonora; Meloni, Alessandra; Murru, Maria Rita; Corongiu, Daniela; Tranquilli, Stefania; Fadda, Elisabetta; Murru, Raffaele; Schirru, Lucia; Secci, Maria Antonietta; Costa, Gianna; Asunis, Isadora; Cuccu, Stefania; et al. (PloS one, 2012)
Vitamin D response elements (VDREs) have been found in the promoter region of the MS-associated allele HLA-DRB1*15:01, suggesting that with low vitamin D availability VDREs are incapable of inducing *15:01 expression allowing in early life autoreactive T-cells to escape central thymic deletion. The Italian island of Sardinia exhibits a very high frequency of MS and high solar radiation exposure. We test the contribution of VDREs analysing the promoter region of the MS-associated DRB1 *04:05, *03:01, *13:01 and *15:01 and non-MS-associated *16:01, *01, *11, *07:01 alleles in a cohort of Sardinians (44 MS patients and 112 healthy subjects). Sequencing of the DRB1 promoter region revealed a homozygous canonical VDRE in all *15:01, *16:01, *11 and in 45/73 *03:01 and in heterozygous state in 28/73 *03:01 and all *01 alleles. A new mutated homozygous VDRE was found in all *13:03, *04:05 and *07:01 alleles. Functionality of mutated and canonical VDREs was assessed for its potential to modulate levels of DRB1 gene expression using an in vitro transactivation assay after stimulation with active vitamin D metabolite. Vitamin D failed to increase promoter activity of the *04:05 and *03:01 alleles carrying the new mutated VDRE, while the *16:01 and *03:01 alleles carrying the canonical VDRE sequence showed significantly increased transcriptional activity. The ability of VDR to bind the mutant VDRE in the DRB1 promoter was evaluated by EMSA. Efficient binding of VDR to the VDRE sequence found in the *16:01 and in the *15:01 allele reduced electrophoretic mobility when either an anti-VDR or an anti-RXR monoclonal antibody was added. Conversely, the Sardinian mutated VDRE sample showed very low affinity for the RXR/VDR heterodimer. These data seem to exclude a role of VDREs in the promoter region of the DRB1 gene in susceptibility to MS carried by DRB1* alleles in Sardinian patients.